Reinventing the Pregnancy Wheel to Improve Pregnancy Dating and Antenatal Care Visits: A Pilot Randomized Trial in Malawi - Mary Stokes; Amber Olson; Mtisunge Chan'gombe; Bakari Rajab; Isabel Janmey; Carolyn Mwalwanda; Judy Levison; Rachel Pope (Global Health and Education Projects, Inc., 2021)
Background and Objectives: The purpose of this study was to evaluate the feasibility of a customized, culturally sensitive pregnancy wheel given to pregnant women to improve gestational age dating accuracy at the time of delivery and to improve antenatal care attendance. Methods: This was a pilot randomized trial involving pregnant women presenting to a regional hospital in Lilongwe, Malawi. The primary outcome was accuracy of gestational age at the time of presentation to the hospital in labor. The secondary outcome was the number of antenatal visits. Results: At final analysis, 14 subjects were included in the pregnancy wheel (intervention) arm and 11 in the standard care arm. Fifty percent (n=7) of women in the intervention arm were accurately dated at the time of presentation for delivery, compared to only 9% (n=1) in the standard antenatal care arm (p=0.04). There was not a significant difference in the number of antenatal visits between the two study arms. No patients met the World Health Organization's recommended eight antenatal care visits for prenatal care. Conclusion and Global Health Implications: The customized pregnancy wheel given to patients could improve gestational age dating accuracy, and as a result, clinical decision making. However, the barriers to greater antenatal care access are more complex and likely require a more complex solution. Significant attrition in this pilot trial limited statistical power, suggesting the need for future larger interventions. Accurate gestational dating requires access to ultrasonography and early antenatal care initiation, both of which are inadequate in Malawi. Although the customized pregnancy wheel did not improve antenatal care attendance, it improved gestational age dating accuracy in a pilot study at a central hospital in Lilongwe, Malawi.   Copyright © 2021 Stokes et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.